A validated finite element model to reproduce Helmholtz's theory of accommodation: a powerful tool to investigate presbyopia. (31st August 2021) - Cabeza‐Gil, Iulen; Grasa, Jorge; Calvo, Begoña
Abstract: Purpose: To reproduce human in vivo accommodation numerically. For that purpose, a finite element model specific for a 29‐year‐old subject was designed. Once the proposed numerical model was validated, the decrease in accommodative amplitude with age was simulated according to data available in the literature. Methods: In contrast with previous studies, the non‐accommodated eye condition was the reference configuration. Consequently, two aspects were specifically highlighted: contraction of the ciliary muscle, which was simulated by a continuum electro‐mechanical model and incorporation of initial lens capsule stresses, which allowed the lens to become accommodated after releasing the resting zonular tension. Results: The morphological changes and contraction of the ciliary muscle were calibrated accurately according to the experimental data from the literature. All dynamic optical and biometric lens measurements validated the model. With the proposed numerical model, presbyopia was successfully simulated. Conclusions: The most widespread theory of accommodation, proposed by Helmholtz, was simulated accurately. Assuming the same initial stresses in the lens capsule over time, stiffening of the lens nucleus is the main cause of presbyopia.